Synthesis, characterization and biological evaluation of N-(2, 3-dimethyl-5-oxo-1-phenyl-2, 5-dihydro-1H-pyrazol-4-yl)benzamides. Issue 105 (13th October 2015) - Saeed, Aamer; Ejaz, Syeda Abida; Khurshid, Asma; Hassan, Sidra; al-Rashida, Mariya; Latif, Muhammad; Lecka, Joanna; Sévigny, Jean; Iqbal, Jamshed
Abstract : Comparison of active site residues of modelled h-GCAP with template h-PLAP. Abstract : We report the synthesis of a series of different substituted N -(2, 3-dimethyl-5-oxo-1-phenyl-2, 5-dihydro-1 H -pyrazol-4-yl)benzamides by making use of a non-steroidal anti-inflammatory drug known as 4-aminophenazone also called as antipyrine, a compound of great interest in drug chemistry. These compounds possess potential biological applications and were screened against human recombinant alkaline phosphatase including human tissue-nonspecific alkaline phosphatase (h-TNAP), tissue specific human intestinal alkaline phosphatase (h-IAP), human placental alkaline phosphatase (h-PLAP) and human germ cell alkaline phosphatase (h-GCAP). These compounds were also tested for their inhibitory potential against recombinant human and rat ecto-5′-nucleotidases (h-e5-NT & r -e5-NT, respectively). All benzamide derivatives inhibited APs to a lesser degree than e5-NT. The reported compounds are of considerable interest for further applications in the field of medicinal chemistry as these compounds have potential to bind nucleotide protein targets.